Randomized controlled trial of stress reduction with meditation and health education in black men and women with high normal and normal blood pressure - Robert H. SCHNEIDER; Clarence GRIM; Theodore KOTCHEN; Komal MARWAHA; Jane KOTCHEN; John W. SALERNO, Ph.D; Carolyn Gaylord KING; Sanford NIDICH; Charles N. ALEXANDER (Elsevier, 2021)
Background: Black men and women suffer from disparities in morbidity and mortality from hypertension, cardiovascular disease, and currently, COVID-19. These conditions are associated with social determinants of health and psychosocial stress. While previous trials demonstrated that stress reduction with meditation lowered BP in the grade I range in Black adults, there is a paucity of evidence for high normal and normal BP. Objective: This randomized controlled trial was conducted to evaluate the effect of stress reduction with the Transcendental Meditation (TM) technique in Black adults with high normal BP and normal BP using international classifications. Methods: A total of 304 Black men and women with high normal (130-139/85-89 mm Hg) and normal BP (120-129/80-84 mm Hg) were randomized to either TM or health education (HE) groups. BP was recorded at 3, 6, 9, 12, 24, 30 and 36 months after baseline. Linear mixed model analysis was conducted to compare the BP change between TM and HE participants in the high-normal BP and normal-BP groups. Survival analysis for hypertensive events was conducted. Results: After an average of 19.9 ± 11.1 months follow-up, TM participants in the high-normal BP group showed significantly lower posttest SBP (-3.33 mm Hg, p = 0.045). There was no difference in DBP (-0.785 mm Hg, p = 0.367) compared to HE participants. In the normal BP group, the SBP and DBP were not different between the TM and HE participants. The hazard ratio for hypertensive events was 0.52 (p = 0.15) in the high normal BP group (7 TM vs 13 HE) with no difference in the normal BP group Conclusion: This RCT found that meditation lowered systolic BP in Black men and women with high normal BP but not in normal BP participants. These results may be relevant to reducing health disparities in CVD and related co-morbidities.